Aplikasi Weigh in Motion Menggunakan Metode Estimasi Untuk Mengukur Beban dan Kecepatan Kendaraan Bergerak - Iif Ahmad Syarif; Abdul Muis Prasetia (Borneo Engineering : Jurnal Teknik Sipil, 2019)
Humans as users of transportation modes, of course, want the ability of vehicles that are able to carry as much cargo as possible and on the fastest trip. This condition often results in the vehicle carrying the maximum load even exceeding the carrying capacity. On this basis and to maximize the results of data collection in the form of traffic volumes and vehicle loads, it is necessary to attempt to check the load of vehicles or trucks passing through the road without causing queues and congestion. To that can be done using a dynamic weighbridge which utilize methods of Weigh In Motion (WIM). The WIM system is equipped with the ability to measure vehicle loads when the truck runs at a certain speed through sensors placed below the road surface. The results showed that the WIM prototype can measure the speed and weight of the vehicle running successfully, the measurement results of running vehicle loads have an average error of 14.9%.